A Study of Aerodynamic Drag of Contemporary Footballs. (2016) - Alam, Firoz; Chowdhury, Harun; Loganathan, Bavin; Mustary, Israt
Abstract: Most modern footballs possess varied surface characteristics which can affect the flight trajectory of the football. Although the aerodynamic behavior of other sports balls have been studied well, little information is available about the aerodynamic behavior of newly introduced footballs with varied seam configurations and number of panels. Therefore, the primary objective of this study is to understand the surface characteristics mainly the seam depth and seam height and their effects on aerodynamic of a range of new generation balls. Four new generation footballs: Kapanya, Cafusa, Tango and Brazuca were selected for this study. Seam length and depth of seam for each ball were measured using 3D scanning technology and also manual measurement. Additionally, the aerodynamic drag forces were measured using wind tunnel over a range of wind speeds for two positions of each ball. It was found that the seam length and depth of seam have influence on the aerodynamic drag of these modern footballs. Results also indicate that the sideway variation of aerodynamic drag is minimal for the Brazuca ball. As a result, this ball may have better stability in flight. The lowest aerodynamic drag was found for the Cafusa ball at high speeds which indicates that this ball is suitable for long distance pass. However, it has highest sideway drag variation that may cause instability in flight.